3y+10=2(-5y+5)-2y

Simple and best practice solution for 3y+10=2(-5y+5)-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+10=2(-5y+5)-2y equation:



3y+10=2(-5y+5)-2y
We move all terms to the left:
3y+10-(2(-5y+5)-2y)=0
We calculate terms in parentheses: -(2(-5y+5)-2y), so:
2(-5y+5)-2y
We add all the numbers together, and all the variables
-2y+2(-5y+5)
We multiply parentheses
-2y-10y+10
We add all the numbers together, and all the variables
-12y+10
Back to the equation:
-(-12y+10)
We get rid of parentheses
3y+12y-10+10=0
We add all the numbers together, and all the variables
15y=0
y=0/15
y=0

See similar equations:

| 1/2(h)-12=-5 | | 3x-41=-2(-2x-7)-6x | | -7y+7(1+2y)=-2y-11 | | (1/2)h-12=-5 | | -8-3(44-5y)=-2y+13 | | 6p+4/6=4p-83 | | 20×x=50 | | -2k-25=2(-4k-39)-1 | | -2x-15=10-2x-25 | | 4^2+20x=0 | | 8n=–6+7n | | 5+7x=-128 | | 7(-3y-5)+9=-8y | | 9x=5x+4(2x-13) | | -10a-24(5a+48)=-2a | | -5+24=-8t-15 | | 11=10(3a+31)+1 | | 3^(2x-3)=4^x | | 12=4(4y-18)-9y | | -43(3z-35)-5=-4z | | (3x-1)(2x-9)=90 | | 8(1)+2y=-6 | | 2(2x-6)-8=4(3x-2) | | 9x-18=5x-2 | | 2b-3b=+4b | | s=0.8(24) | | 6912=(18x+6x)*18x | | 3x^2+6x+2=4 | | b=(0.75)90 | | 10.1x-1.6x+44=7 | | x+5x-5+5x-5=122 | | 6−9x=-120 |

Equations solver categories